PARADIGMA PEMBANGUNAN EKONOMI; SATU ANALISIS TINJAUAN ULANG DARI PERSPEKTIF EKONOMI ISLAM - SYAMSURI SYAMSURI (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri (UIN), 2016)
Abstract. Paradigm of Economic Development; Perspective of Islamic Economics Analysis. The capitalist economic system has failed because the rich exploiting the poor and a socialist economic system justifies the poor seize property of the rich. This problem becomes an important issue for the Muslim economists. Paradigm both the liberal system is exploitative, unfair and treats people not as people. Not pay attention to moral values and akhlaqs, a dichotomy between religion and economics, make man a slave of development and not development for human. This paper is a reflection phenomenon of damage to the environment, social inequality and poverty not been abated. So the liberal economic theories and concepts need to be reviewed by presenting a new economic development concept that comes from revelation that is the Quran and hadith. Finally, from the discussion can be concluded that economic development can not be achieved except with implementing Islamic guidance in everything. And the nature of development must necessarily multi-dimensional, included the gratification of physical and ruh. Economic development must also be able to create a balance between individual interests and the interests of society, kindness balanced and consistent according the rules of Islam. Measure of the success of development if the concept of caliphate, ‘adalah, and tazkiyah can meet all basic needs of every human being and nature conservation around for the long term future generations.Abstrak. Paradigma Pembangunan Ekonomi; Satu Analisis Tinjauan Ulang Dari Perspektif Ekonomi Islam. Kegagalan sistem ekonomi kapitalis yang membenarkan orang kaya mengeksploitasi orang miskin, dan sistem sosialis membenarkan orang miskin merampas harta orang kaya menjadi satu isu penting bagi para ekonom muslim. Paradigma kedua sistem liberal tersebut bersifat eksploitatif dan tidak fair serta memperlakukan manusia bukan sebagai manusia. Mengesampingkan nilai moral dan akhlak, memisahkan antara agama dengan ekonomi, dan menjadikan manusia hamba pembangunan, bukan pembangunan untuk manusia. Makalah ini merupakan satu refleksi fenomena dari kerusakan alam, ketimpangan sosial, kemiskinan yang tidak berkunjung reda. Sehingga teori dan konsep ekonomi liberal perlu ditinjau ulang dengan menyajikan satu konsep pembangunan ekonomi baru yang bersumber dari wahyu yaitu al-Quran maupun hadith. Akhirnya dari pembahasan dapat disimpulkan bahwa pembangunan ekonomi tidak akan dapat dicapai melainkan dengan menjalankan ajaran Islam secara kaffah, dan sifat pembangunan mestilah multi dimensi yang merangkumi pemuasan secara fisik maupun ruh. Termasuk pembangunan ekonomi juga mesti dapat menciptakan keseimbangan antara kepentingan individu dan kepentingan masyarakat, kebaikan yang seimbang dan konsisten sesuai kaedah-kaedah agama Islam. Tolak ukur keberhasilan pembangunan ini apabila tuntutan khilafah, ‘adalah dan tazkiyah dapat memenuhi seluruh keperluan dasar setiap insan dan pelestarian alam sekitar untuk jangka panjang generasi selanjutnya.